Connecting genetic risk to disease end points through the human blood plasma proteome - Karsten Suhre (Nature Portfolio, 2017)
Individual genetic variation can affect the levels of protein in blood, but detailed data sets linking these two types of data are rare. Here, the authors carry out a genome-wide association study of levels of over a thousand different proteins, and describe many new SNP-protein interactions.